2021
DOI: 10.2174/1567205018666210906092940
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Cholesterol Regulation of LRP1 and RAGE on Aβ Transport Across the Blood-Brain Barrier in Alzheimer’s Disease

Abstract: Background: High cholesterol aggravates the risk development of Alzheimer's disease (AD). AD is closely related to the transport impairment of amyloid-β (Aβ) in the blood-brain barrier. It is unclear whether high cholesterol affects the risk of cognitive impairment in AD by affecting Aβ transport. The purpose of the study is to investigate whether high cholesterol regulates Aβ transport through low-density lipoprotein receptor-related protein 1 (LRP1) and receptor for advanced glycation end products (RAGE) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…Accordingly, PCSK9 inhibition was shown to reduce neuronal apoptosis [ 54 ]. On the other hand, the cholesterol depletion hypothesis is in full accordance with the results of in vivo animal studies, in which silencing of lipoprotein receptors, implicated in cholesterol uptake and target of PCSK9, led to cognitive impairment [ 55 , 56 , 57 , 58 , 59 ], which was likely related to neuronal loss. Notably, as reported by Oliveira J. et al, the cognitive impairment observed in LDLr −/− mice was associated with neuronal apoptosis in brain regions related to memory formation [ 58 ].…”
Section: Discussionsupporting
confidence: 80%
“…Accordingly, PCSK9 inhibition was shown to reduce neuronal apoptosis [ 54 ]. On the other hand, the cholesterol depletion hypothesis is in full accordance with the results of in vivo animal studies, in which silencing of lipoprotein receptors, implicated in cholesterol uptake and target of PCSK9, led to cognitive impairment [ 55 , 56 , 57 , 58 , 59 ], which was likely related to neuronal loss. Notably, as reported by Oliveira J. et al, the cognitive impairment observed in LDLr −/− mice was associated with neuronal apoptosis in brain regions related to memory formation [ 58 ].…”
Section: Discussionsupporting
confidence: 80%
“…(low-density lipoprotein receptor-related protein 1)Low-density lipoprotein receptor-related protein 1 is required for survival of oligodendrocyte progenitor cells (OPC) (Schäfer et al, 2019). Since cholesterol can down-regulate LRP1 (Zhou et al, 2021), this could potentially impair function of OPCs and impair myelin repair. OPCs require LRP1 to maintain normal cholesterol and require LRP1 to differentiate into mature oligodendrocytes (OLs) (Lin et al, 2017).…”
Section: Lrp1mentioning
confidence: 99%
“…Low-density lipoprotein receptor-related protein 1 is the main transporter for Abeta out of cells and out of brain via the BBB (Shibata et al, 2000;Zlokovic et al, 2010). Hypercholesterolemia decreased LRP1 expression, which would decrease Abeta efflux across the BBB, and increased RAGE expression, which would increase Abeta influx through the BBB, in cerebral endothelial cells (Zhou et al, 2021). Hypercholesterolemia increased brain apoptosis in AD mice.…”
Section: Cholesterol Effects On Abeta Transportersmentioning
confidence: 99%
“…LRP1 plays a vital role in the pathological process of AD. The BBB plays an important role in the mechanism of transporting clearance of Aβ in AD, and LRP1 is a key receptor for the BBB to transport Aβ, and one of its functions in the brain endothelium is to transport Aβ from brain tissue to blood circulation, thus playing a role in clearing Aβ in the brain (Zhou et al., 2021 ). Moreover, the recently reports suggested that TSIIA was able to improve protein expression of glucose transporter 1 (GLUT1) and LRP1, thereby improving pathological progression in AD mice (Ma et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%